A hatalom megosztottsága - Horváth M., Tamás (Tér és Társadalom, 1992)
The problems of the division of power between the metropolitan bodies and civil servants. This study was prepared as part of the analysis initiated for the preparation of the reform of the local-authority system of the capital city of Budapest. One of the main lines in the analysis is the screening of the internal structure of Budapest after 1990. The study analyses with empirical methods the post-transformation development and its consequences. The general assembly of the capital city practices the rights of the local authority. As opposed to the previous, Soviet-type council, it has a real power. The body which became legitimate at the free, multi-party elections, has the right to develop its own political strategy in order to fulfill its duties and to organize the supply of public services in Budapest. This body is also the „number one" depositor of legal authorities, as it has the right to decide on the relegation of power to one of its bodies, and also on the control of meeting the duties. According to the experiences, the general assembly took its role seriously. In an annual average, the assembly meets every other week. At an average meeting, 10-30 issues are on the agenda. The meetings are from 9 a.m. to the evening, and accidentally to late at night. Postponement (continuing the dispute the next day) is also common. During the first two years of the term, more than 50 resolutions were made, on an average, at one meeting. The impressive data, however, are also clear proof of being over-burdened. It is an open issue, whether this much of work is adequate to the load-bearing capacity of a body with 90 members. The detailed analysis actually referred to duplications and parallels in the system. 1. (Managers and managerial levels) A kind of fight developed between the bodies and their elected civil servants concerning the scopes of their authority. According to law, the general assembly has the right to relegate some of the local-authority issues to the lord mayor. However, as the executive bodies are not clearly supported by the majority of the bodies, special compromises were made. In general, the general assembly kept the majority of the operational executive authorities. Settling the relationship at an institutional level between the the lord mayor, as the head of the local authority on the one hand, and the chief notary, as the direct head of the office, also took a long time. It was so, because according to the law, the lord mayor is not only a political leader, but also the head of the apparatus itself. At the same time, however, it is the chief notary who is responsible for the professional nature and legality of the work done in the office. The supervision of the big areas of supply has been divided among the deputy lord mayors. The chairmen of the newly setup committees were given different roles. Though the general assembly did not relegate too many of the real authorities to them either, they were still put into important supervisory positions concerning the management of the office and the relevant departments. The intentions of the managers of the office to preserve the body’s integrity and unity are often crossed by the activity of the committees. 2. (The organization of the office) During the first halt of the term, namely between 1990 and 1992, the office was transformed considerably. More than halt of the staff lett. The change was even more significant among the managers: 80% of them are new in their position. The structure of the office is not the same, either. Some departments disappeared, while new were formed. Nevertheless, the total number of the civil servants decreased with 13 % during 2 years. Within this, the number of those working at the traditional, sectoral and functional departments has decreased more. At the same time, the weight of the core staff units directly helping the managers, increased. The oppositional parties criticise the excessive number of the experts employed, and the big size of the consultative bodies. At the same time, this kind of restructuring of the office is coupled with the strengthening of new, nontraditional techniques of administration, like, for example, program management. As opposed to the mechanism based on rigid department structure, this is the result of a conscious developement. 3. (Committees and factions) In the preparation of political decisions, the committees and the party factions compete with each other. Many of the committees actually want to reach a strong position, and do it, often enough, with success. Charismatic leaders give a clear feature to the political practice of a part of the capital city. On the other hand, however, the party policy intentions are coordinated through the organizational system of the factions. The five parties present in the general assembly of the capital city exercise strong and often well-elaborated faction activities. In addition, the role of the parties in the decision-making process is accepted and institutionalized by the organizational and operational rules as well. The key point of the tensions within the organization is the status of the committees. Nevertheless, the committees hardly substitute the general assembly, and hardly take their duties over, as authority in merít was not really given to them. However, certain committees (Ownership committee, Health and Sports committee, etc.) could still get, through individual bargains, a decisive role. On the other hand, however, the role of the committees is clearly significant in the management and control of the departments. Nevertheless, this weakens the operational positions of the cheaf heads of the general assembly, namely those of the lord mayor and his surroundings. Up till now, several attempts were made to solve the organizational conflicts. However, no agreement was made. This is due to two reasons. On the one hand, to the political structure of the capital city, which condemns the strongest party to minority government. On the other hand, the structure of the local authority itself makes the solution of the internal conflicts difficult, and this would be so, even if there was majority governing at the local authorities. Finally, the study is concluded with certain general proposals. The solution is evidently the consequent following of one of the international urban management practices. „One perlon cannot ride two horses at the same time", which means that it is impossible to have, at the same time, a strong, intervening body of representatives, and a separate, operative execution.